2017
DOI: 10.1177/1057567716683776
|View full text |Cite
|
Sign up to set email alerts
|

Factors Impacting Job Satisfaction Among Police Personnel in India

Abstract: Job satisfaction is important for both the employee and organization. Theories of motivation and job satisfaction have been applied in the context of police organizations, providing insight into organizational dynamics. On the basis of multivariate analysis of data collected from 500 police personnel in India, this article attempts to understand the impact of demographic factors, organizational, and job characteristics on job satisfaction. While some findings conform to existing research on job satisfaction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 81 publications
1
14
0
Order By: Relevance
“…There have been mixed findings on the impact of education on job satisfaction with some studies reporting a positive impact of education on job satisfaction (Dantzker, 1992; Roberg & Bonn, 2004), and other studies finding no significant impact (Buzawa et al, 1994; Johnson, 2012; Miller et al, 2009; Paoline et al, 2015; Zhao et al, 1999). However, studies conducted in India did not find any impact of education on job satisfaction (Kumar, 2017; Lambert et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 87%
See 3 more Smart Citations
“…There have been mixed findings on the impact of education on job satisfaction with some studies reporting a positive impact of education on job satisfaction (Dantzker, 1992; Roberg & Bonn, 2004), and other studies finding no significant impact (Buzawa et al, 1994; Johnson, 2012; Miller et al, 2009; Paoline et al, 2015; Zhao et al, 1999). However, studies conducted in India did not find any impact of education on job satisfaction (Kumar, 2017; Lambert et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 87%
“…Robie et al (1998) have attributed the impact of rank on job satisfaction to the power distance among the ranks and recommend that the reduction of power distance would reduce the difference in job satisfaction. Research in India has reported mixed findings with Lambert et al (2015) finding no impact of rank on job satisfaction and Kumar (2017) reporting a significant relationship between the variables.…”
Section: Literature Reviewmentioning
confidence: 96%
See 2 more Smart Citations
“…Second, most of the recent research on police officers’ job satisfaction is from outside the United States. For example, studies have been conducted in countries such as India (e.g., Kumar, 2017; Lambert, Qureshi, Frank, Klahm, & Smith, 2018), China (e.g., Chen, 2018), Serbia (Zekavica, Simeunovic-Patic, Potgieter, & Roelofse, 2018), Slovenia (Aristovnik, Seljak, & Tomaževič, 2016; Tomaževič, Seljak, & Aristovnik, 2014, 2019), Turkey (Kula, 2017), and Pakistan (Ahmad & Islam, 2019). These international studies have contributed to the general scholarly understanding of officer job satisfaction, but policing in the United States differs markedly from that in other countries.…”
Section: Introductionmentioning
confidence: 99%